Konstruksi Nilai-Nilai Pendidikan Islam dalam “Ada Pappaseng” Masyarakat Suku Bugis Desa Terpedo Jaya Kecamatan Sabbang Selatan Kabupaten Luwu Utara - Husnah, Magfiratul; Kartini, Kartini; Arifuddin, Arifuddin (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This research is motivated by the observable reality in the modern era, marked by rapid globalization and modernization, which has led to the gradual fading of noble values such as those embodied in “Ada Pappaseng” especially in Terpedo Jaya Village. The study explores the construction of Islamic educational values within the “Ada Pappaseng” tradition of the Bugis community in Terpedo Jaya Village, South Sabbang Subdistrict, North Luwu Regency. The objectives of this research are to identify the forms of “Ada Pappaseng” in the Bugis community of Terpedo Jaya and to analyze the correlation between Islamic educational values and “Ada Pappaseng”. This study employs a qualitative approach with an ethnographic research design to gain an in depth understanding of the social phenomena. Data were analyzed using a hermeneutic approach through three stages: data reduction, data interpretation, and conclusion drawing. The findings reveal that “Ada Pappaseng” in the Bugis community of Terpedo Jaya Village is conveyed both orally and in written form, primarily through two main styles: warekkada (figurative expressions) and monologues. The integration of Islamic educational values in “Ada Pappaseng” is evident in three core aspects: theological (aqidah) values, moral (akhlak) values, and devotional (ibadah) values. Theological values are reflected in teachings about belief in destiny and maintaining faith in all aspects of life. Moral values are seen in the promotion of trust in God (tawakkal), honesty, responsibility, respect for parents, and the prohibition of reprehensible traits such as envy and slander. Devotional values are evident in messages emphasizing the importance of prayer, spiritual purity, and nurturing the soul to submit fully to Allah (SWT).